Long‐term testosterone undecanoate replacement therapy: Impact of ethnicity. (29th January 2020) - Kempegowda, Punith; Quinn, Lauren M.; Chandan, Joht Singh; Shepherd, Lisa; Kauser, Samina; Rahim, Asad; Bates, Andrew
Abstract: Background: Testosterone replacement therapy (TRT) is indicated for symptomatic male hypogonadism. However, the safety and efficacy profiles across different ethnicities for long‐term TRT remain unclear. Objective: To measure the impact of ethnicity on various biochemical parameters following testosterone undecanoate (TU) replacement. Method: A retrospective analysis of 50 male patients treated with TU from 2006 to 2017 in a large secondary care centre was performed. Changes in total testosterone, PSA, haematocrit, haemoglobin, total cholesterol and low‐density lipoprotein (LDL) over eight years of treatment were analysed. Wilcoxon rank sum test was used to assess differences in these parameters between Caucasians and South Asians. Results: Thirty‐one Caucasians (age: median (IQR) 55.0 years (49.0‐68.0); total duration of follow‐up 6.1 years (2.9‐9.3)) and 19 South Asians (age: median (IQR) 52.0 years (38.0‐69.0); duration of follow‐up 6.5 years (1.3‐8.4)) were treated with TU during the study period. There was no significant difference in total testosterone levels between the two ethnicities. We noted a higher free and bioavailable testosterone in South Asians than Caucasians, albeit within their reference range. PSA was higher in Caucasians than South Asians at two and eight years of TU therapy. After one year of TRT, haematocrit was higher in South Asians than Caucasians at one year, whereas LDL and total cholesterol were significantly higher in Caucasians than South Asians. Conclusions: Caucasians have a tendency towards increased PSA, total cholesterol and LDL compared with South Asians with TU replacement therapy. There is a higher increment of haematocrit in South Asians following one year of TU replacement therapy. All biochemical changes following TRT were within the respective reference ranges suggesting no apparent risk of prostate cancer and venous thromboembolism.